How we established a multidisciplinary program for vascular anomalies. (7th September 2022) - Borst, Alexandra J.; Swerdlin, Rachel F.; Phillips, James D.; Hawkins, C. Matthew; Briones, Michael A.
Abstract: The care of patients with vascular anomalies is quickly becoming a complex field requiring high‐quality, coordinated multidisciplinary care. In this article, we review the history of multidisciplinary care in this field, discuss the benefits of this model of care, and outline some of the essential components and structure of a successful vascular anomalies team. We provide an overview of two example programs and a roadmap for other centers to develop their own multidisciplinary vascular anomalies teams.